Participative multilingual identity construction in the languages classroom: a multi-theoretical conceptualisation. Issue 4 (1st October 2020) - Fisher, Linda; Evans, Michael; Forbes, Karen; Gayton, Angela; Liu, Yongcan
ABSTRACT: Multilingual identity is an area ripe for further exploration within the existing extensive body of identity research. In this paper we make a case for a conceptual framework that defines multilingual identity formation in terms of learners' active involvement, and proposes the classroom as the hitherto underused site for participative identity (re)negotiation. After reviewing three key theoretical perspectives on identity (the psychosocial, sociocultural and poststructural) for points of intersection and difference, we propose a new framework for a multi-theoretical approach to the conceptualisation and investigation of multilingual identity. This places it at the nexus of (a) individual psychological development, (b), the relational and social, and (c) the historical and contextual. Arguing that a participative perspective can take the field forward, we present a theorised model for classroom practice that provides a structure within which individual learners of a foreign language might explore, with reference to a range of sociolinguistic knowledge, the extent of their current linguistic repertoire. In addition, they are asked to explicitly consider their identity and identifications and offered the agency to (re)negotiate these in terms of multilingual identity, the development of which may be important for investment in language learning.